NCMP-03. ANATOMIC AND SURGICAL FACTORS PREDICT DEVELOPMENT OF LEPTOMENINGEAL DISEASE IN PATIENTS WITH METASTATIC MELANOMA. (12th November 2021) - Lowe, Stephen; Wang, Christopher; Brisco, Amanda; Arrington, John; Ahmed, Kamran; Vogelbaum, Michael; Liu, James
Abstract: Leptomeningeal disease (LMD) is a devastating complication of systemic malignancy, portending a poor prognosis with an estimated median survival of 4-6 weeks if left untreated. Several reports have suggested surgical resection as a potential causative factor. Herein, we explore if surgical and anatomical factors are correlated with development of LMD in patients with melanoma brain metastases. METHODS: Patients treated at our institution between 1999-2019 for primary melanoma with brain metastasis were compiled into a database based on ICD9/10 coding. 1, 079 patients with melanoma brain metastases and appropriate imaging were identified, and 834 patients with a minimum of 3 months' follow up were included. Patients were dichotomized by development of LMD or lack thereof, and categorized into an overall cohort, and surgical and non-surgical cohorts. Anatomic factors and ventricular access during surgery were investigated as possible correlative factors for the development of LMD. RESULTS: In the overall cohort, female gender(p=0.033), presence of dural metastasis(p=0.018), presence of periventricular lesions(p< .001), presence of intraventricular lesions(p< .001), and ventricular access during surgery(p< .001) were significantly associated with LMD. Patients undergoing surgery, or those undergoing surgery without ventricular access, were not at higher risk of LMD. On multivariate analysis, female gender(p=.033), presence of periventricular lesions (p< .001), presence of intraventricular lesions(p< .002), and presence of dural metastasis(p=0.032) were significantly associated with development of LMD. In patients who had surgery, iatrogenic ventricular access(p< .001) was significantly correlated with LMD. In the group of patients without surgery, those with periventricular lesions had significantly higher odds of LMD(p< .001). CONCLUSIONS: In a retrospective cohort of patients with melanoma metastatic to the brain, surgical intervention does not increase odds of LMD; however, iatrogenic access to the CSF space during surgery is highly correlated with LMD development. Anatomic contact with the CSF space predicts LMD regardless of surgical status.